Sporadic Hemangioblastoma of the Cavernous Sinus and Meckel's Cave - Kord Valeshabad, Ali; Xiao, Lekui; Amin-Hanjani, Sepideh; Alsadi, Alaa; Valyi-Nagy, Tibor; Kim, Jinsuh (Journal of Neurological Surgery Reports, 2018)
Objectives To describe an extremely rare case of sporadic hemangioblastoma (HB) within the cavernous sinus and Meckel's cave with extension to the cerebellopontine angle (CPA) cistern.Methods A 73-year-old male presented with hearing loss, unilateral ptosis, and facial numbness.Results The imaging showed a complex cystic-solid mass centered at the left cavernous sinus and Meckel's cave with extension to the CPA cistern. Patient underwent retrosigmoid craniectomy for partial resection of the CPA angle component of the mass. Surgical pathology confirmed the diagnosis of HB and patient was scheduled for subsequent radiotherapy of the residual mass.Conclusions We present an exceptional case of supratentorial HB without associated von Hippel–Lindau (VHL) disease, which was predominantly located in the cavernous sinus and Meckel's cave and led to multiple cranial nerve symptoms. We describe imaging characteristics and radiologic–pathologic correlation of this atypically located HB, which can be difficult to consider in the differential diagnosis presurgically.
Keywords: hemangioblastoma; cavernous sinus; Meckel's cave; cerebellopontine angle; denervation atrophy